The Relation Between Fisheries Counseling Capacity and Fisherman Satisfaction in Counseling Activities in Batang Gasan, Padang Pariaman Regency, West Sumatera Province - Zulkarnain, Zulkarnain; Metalisa, Rindi; Mahrunnisa, Mahrunnisa (Faculty of Fisheries and Marine Science, Brawijaya University, 2024)
Batang Gasan District, Padang Pariaman Regency, West Sumatra Province has a fisheries product processing segment, both in terms of human resources (interest and experience) and natural resources (fisheries production). The purpose of this study was to determine the capacity for counseling for fisheries workers, fishermen’s satisfaction, and the relationship between the capacity of fisheries counseling workers and fishermen satisfaction in counseling related activities. Respondents in this study were fishermen who participated in counseling activities, as many as 68 people were used as samples using accidental sampling. The data analysis technique uses the Spearman Rank correlation method (Rs). In which, the results of this study are the capacity of counseling workers as facilitators is considered good, the capacity of counseling workers as motivators and educators is considered not good and the capacity of counseling workers as communicators is considered quite good, fishermen's satisfaction with planning is considered as quite satisfied, fishermen's satisfaction with implementation and evaluation is considered as not satisfied, and the capacity of counseling workers as facilitators, motivators, educators and communicators is significantly related to fishermen's satisfaction. It is expected that the capacity of counseling workers as motivators and educators is further enhanced in counseling activities so that fishermen feel satisfaction and can make fishermen's behavior change.